Integration of substrate in aluminium wire and arc additive manufacturing - Eimer, Eloise (Cranfield University, 2019)
Integrating wrought alloys into a wire and arc additively manufactured component is very beneficial in order to reduce the duration and cost of deposition. However the microstructure and therefore mechanical properties of the wrought and deposited materials will be different. This thesis reports on a study of the properties of integral parts made of a combination of wrought alloy and material deposited by Wire and Additive Manufacture. The study was divided into two parts. Firstly, high strength aluminium alloys were additively manufactured and studied. Secondly, the interface between additive manufactured material and wrought alloys was examined. Aluminium copper magnesium alloy was deposited by wire and arc, and its microstructure and mechanical properties were characterised using optical microscopy, scanning electron microscopy, and tensile tests in as-deposited, inter-pass rolled and heat treated conditions. In the as-deposited condition, the mechanical properties achieved were significantly lower than those of wrought material, with a yield strength up to 150 MPA lower than this achieved by heat treated wrought alloy. After heat treatment to the T6 temper, the inter-pass rolled WAAM material properties in the horizontal direction were similar to these of wrought products but with a high anisotropy. An investigation into depositing aluminium zinc alloys using the novel process of laser-assisted wire and arc. The process was studied using a video camera and a device measuring the electric arc characteristics. Optical and scanning electron microscopy were used to analyse the deposited material quality. The potential of the laser-assisted wire and arc process for deposition of zinc alloys was successfully demonstrated by depositing some three layer high structure in aluminium zinc with a very high zinc content. To examine the properties of the interface between deposited and wrought material, a large number of alloys from different aluminium alloy families, were used as substrates and wires. The microstructures of the interfaces were characterised using optical and scanning electron microscopy. The mechanical properties were evaluated using micro hardness, tensile test and digital image correlation. Combinations including aluminium lithium and aluminium zinc wrought alloys resulted in specific issues at the interface, such as porosity or hot cracking. However in general the interface did not have a detrimental effect on the interface yield strength which was the same as the yield of the deposited material. In the as-deposited condition, the maximum tensile properties were limited only by the deposited material or by the heat affected zone which depended on the substrate. Heat treatment made possible the partial or total recovery of the properties in the heat affected zone in the substrate. The mechanical properties of the deposited material were also drastically improved, resulting in a heat treated interface with higher mechanical properties than in the as-deposited condition. Inter-pass rolling reduced the level of porosity in the deposited material and could reduce the formation of cracks in between the first and second layer. However, the rolling of the first layer were an issue because of the proximity of the substrate and the resulting change in bead geometry. This can lead to lower mechanical properties in this area and could be detrimental to the properties of the interface. This project was funded by Constellium Technology Center.
PhD in Manufacturing